Penerapan Sistem Pendukung Keputusan dalam Pemilihan Supplier dengan Metode TOPSIS - Gunawan, Rakhmat Dedi (Journal of Information Technology, Software Engineering and Computer Science (ITSECS), 2024)
Supplier selection is an important process in supply chain management that aims to select the best business partners who are able to provide goods or services according to the company's needs with optimal quality, price, and delivery time. Problems in selecting suppliers often arise due to the complexity of the evaluation process involving various conflicting criteria. The main purpose of this study is to produce a more accurate and objective supplier ranking based on various criteria, such as product quality, price, delivery time, order flexibility, and payment terms. With this approach, this research can improve decision-making efficiency by minimizing subjectivity and bias in the supplier evaluation process. This research contributes to the development of a decision support system based on a multi-criteria method, especially in the context of supply chain management and business partner selection. The results of the calculation using the TOPSIS method, the alternative ranking for supplier selection is determined by the proximity value calculated from the distance of each alternative to the positive and negative ideal solution. Supplier 7 ranked first with the highest proximity value, 0.7653, indicating that this supplier is closest to the ideal solution. It was followed by Supplier 3 in second place with a proximity value of 0.7112, which also had a good performance although slightly lower than Supplier 7. The results of this ranking provide a clear picture of which suppliers best meet the desired criteria, making it easier to make decisions.